The DESIGN OF AVANT-GARDE FASHION INSPIRED BY PIAZZA SAN PIETRO WITH MANIPULATING PLEATS AND WEAVING - Pasaribu, Lili Sonata; Indarti, Indarti (Home Economics Journal, 2026)
The rapid development of fashion is influenced by societal needs, culture, and lifestyle. One of the styles that has evolved in response to these dynamics is avant-garde fashion, which emphasizes freedom of expression through the use of extreme and nonconventional materials, forms, and designs. The design of avant-garde fashion inspired by Piazza San Pietro using manipulating pleats and weaving techniques represents an exploration of this stylistic approach. This study aims to examine the process and final results of designing avant-garde fashion inspired by Piazza San Pietro through the application of manipulating pleats and weaving techniques. The research employs the double diamond method, which consists of four stages: discover, define, develop, and deliver. The discover stage involves identifying sources of inspiration. The define stage focuses on determining the main concept and translating it into a moodboard. The develop stage includes the creation of design illustrations, design development, and exploration of details and prototype forms. The deliver stage involves evaluating the final product by experts. The research was conducted at the Fashion Design Laboratory of the Faculty of Vocational Studies. Data were collected through observation by three experts in the field of fashion design using observation sheet instruments. Data analysis was carried out using quantitative descriptive analysis by calculating the mean or average value. The results indicate that the avant-garde fashion design inspired by Piazza San Pietro achieved an overall average score of 4.22, categorized as very good. The avant-garde silhouette aspect obtained a score of 4.33 (very good). The conceptual suitability aspect scored 4.00 (good). The creativity and innovation aspect scored 4.00 (good). The application of manipulating pleats and weaving techniques scored 4.00 (good). The suitability of color and materials achieved a score of 4.33 (very good). The visual appearance on the runway received a score of 4.67, categorized as very good overall.